2017
DOI: 10.1515/popore-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of large zooplankton sampled with two different gears during midwinter in Rijpfjorden, Svalbard

Abstract: During a midwinter cruise north of 80 o N to Rijpfjorden, Svalbard, the composition and vertical distribution of the zooplankton community were studied using two different samplers 1) a vertically hauled multiple plankton sampler (MPS; mouth area 0.25 m², mesh size 200 μm) and 2) a horizontally towed Methot Isaacs Kidd trawl (MIK; mouth area 3.14 m², mesh size 1500 μm). Our results revealed substantially higher species diversity (49 taxa) than if a single sampler (MPS: 38 taxa, MIK: 28) had been used. The youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Methot Isaac Kidd (MIK) sampling was performed both in Rijpfjorden in fall and in winter for an adjacent project but the samples were analyzed using different methods and levels of expertise. We therefore prefer to discuss our results by referring to past studies and other manuscripts, which have investigated the community composition and abundance of zooplankton in a range of fjords in Svalbard allowing us to make well‐informed inferences (Bandara et al, ; Błachowiak‐Samołyk et al, ; Cusa, ; Dalpadado et al, ; Geoffroy et al, ; Kraft, Berge, Varpe, & Falk‐Petersen, ). Furthermore, bioenergetic measurements of the potential prey would help elucidate whether, all else being equal, there is an advantage to select for a given prey over other available prey (But see Mayzaud & Boutoute, ).…”
Section: Discussionmentioning
confidence: 99%
“…Methot Isaac Kidd (MIK) sampling was performed both in Rijpfjorden in fall and in winter for an adjacent project but the samples were analyzed using different methods and levels of expertise. We therefore prefer to discuss our results by referring to past studies and other manuscripts, which have investigated the community composition and abundance of zooplankton in a range of fjords in Svalbard allowing us to make well‐informed inferences (Bandara et al, ; Błachowiak‐Samołyk et al, ; Cusa, ; Dalpadado et al, ; Geoffroy et al, ; Kraft, Berge, Varpe, & Falk‐Petersen, ). Furthermore, bioenergetic measurements of the potential prey would help elucidate whether, all else being equal, there is an advantage to select for a given prey over other available prey (But see Mayzaud & Boutoute, ).…”
Section: Discussionmentioning
confidence: 99%
“…Basedow et al (2018) observed that the transport of North Atlantic Water into the Arctic is larger during the Polar Night (January) than in May and August, and that there is a strong influx of zooplankton with North Atlantic Water during the Polar Night. They observed an influx of the bioluminescent copepod Metridia longa, which remains active during the Polar Night, and it has a relatively deep distribution (> 150 m; Blachowiak-Samolyk et al 2015, 2017. Indeed, Hop et al 2019 reported similar processes contributed to higher abundance of Metridia longa and ostracods (known to be bioluminescent, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Then each individual was placed in ethanol for further molecular species identification. Calanus hyperboreus as a deep-water, oceanic species 49 51 is very rarely caught in planktonic nets dedicated for sampling mesozooplankton fraction 52 . It is mainly associated with Greenland waters constituing substantial component of chick diets in the eastern 32 , 53 , 54 and northwest Greenland 55 , 56 .…”
Section: Methodsmentioning
confidence: 99%